2020
DOI: 10.3390/ijerph17051562
|View full text |Cite
|
Sign up to set email alerts
|

Spanish Validation of the Internet Gaming Disorder Scale–Short Form (IGDS9-SF): Prevalence and Relationship with Online Gambling and Quality of Life

Abstract: Online gaming is a very common form of leisure among adolescents and young people, although its excessive and/or compulsive use is associated with psychological impairments in a minority of gamers. The latest (fifth) edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5, Section III) tentatively introduced Internet Gaming Disorder (IGD). Since then, a number of evaluation tools using the DSM-5 criteria have been developed, including the Internet Gaming Disorder Scale–Short Form (IGDS9-SF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
70
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(78 citation statements)
references
References 71 publications
2
70
1
5
Order By: Relevance
“…Considering the significant growth of mobile gaming, it seems important to learn about its potential risks. Following Pontes and Griffiths (2015) [12], we have estimated the prevalence of IGD in our study sample as 3%, which is similar to the 1.9% and 2.6% found in other Spanish samples [66,69]. The results of our study fall within the prevalence rate range reported by other international studies.…”
Section: Prevalence Of Igd In Mobile Gamerssupporting
confidence: 90%
“…Considering the significant growth of mobile gaming, it seems important to learn about its potential risks. Following Pontes and Griffiths (2015) [12], we have estimated the prevalence of IGD in our study sample as 3%, which is similar to the 1.9% and 2.6% found in other Spanish samples [66,69]. The results of our study fall within the prevalence rate range reported by other international studies.…”
Section: Prevalence Of Igd In Mobile Gamerssupporting
confidence: 90%
“…The final version of the scale used in the present study is shown in Appendix A , Table A1 . Discrepancies between this translation and Beranuy et al’s [ 42 ] version were minimal, and both retained the core psychological meaning of the original English version. The Cronbach’s alpha and the Omega coefficients for the IGDS9-SF in the present study were α = 0.90 and ω = 0.84, respectively.…”
Section: Methodsmentioning
confidence: 82%
“…However, a recent study [ 47 ] suggested that using a cut-off of 32 points on the IGDS9-SF yields robust diagnostic capabilities (i.e., Youden’s index, 96.2%; diagnostic accuracy, 96.1%; sensitivity, 98%; specificity, 91.9%; negative predictive value, 100%; accuracy, 96.1%). Despite these potential limitations, the present study expands the previous work by Beranuy and colleagues [ 42 ] on the utility of the Spanish version of the IGDS9-SF, as it utilized a community-based sample across a wide age range (adolescents and adults). Another important contribution of the present study is that it provided necessary data on the IGDS9-SF’s temporal stability and incorporated IRT as a framework of analysis.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations